Avaliação de parâmetros físico-químicos e microbiológicos da água armazenada em cisternas de placas e de polietileno no agreste paraibano - Dias, Jobson Targino (2016)
The captation and storage of rain water in precast concrete and polyethylene tanks have been widely disseminated in the Brazilian semiarid region. In drought that began in 2012, tanks installed in the context of government programs received frequent contributions from water of fluvial reservoirs transported by water trucks. This research aims to evaluate the quality of water stored on concrete tanks and polyethylene and their suitability for domestic use in homes in the Agreste semiarid area of the Paraiba State. Another aim is also to compare the differences between the quality of water stored in two types of tanks. It was used as a reference for compliance of water for human consumption the ordinance No. 2,914 / 2011 of the Ministry of Health (MS) and its potability standards. Physico-chemical and bacteriological analyzes were performed, as well as the determining the quality Bascarán water index in the water stored in tanks monitored in São Sebastião de Lagoa de Roça- Paraíba. Measurements were made on 10 concrete tanks and 9 of polyethylene for 10 months. Virtually no differences could be considered relevant among the measured physicochemical parameters in the water in the two types of tanks. The exception was on the alkalinity, pH and hardness parameters. The results for these parameters, in general, are in compliance with the recommended values in Ordinance No. 2914/2011 of MS. The lowest percentages of compliance occurred in polyethylene tanks for the pH parameter, with 70.5% coverage and color with 89.3% and 90.4% for the concrete tanks and polyethylene respectively. It was found that there was the presence of total coliforms in all samples, which indicates the need for treatment for human consumption. The average test performed between the values of Bascarán Water Quality Index related to water stored in two types of tanks concluded that there is no statistical significance to state that the average IQAb between the concrete tanks and polyethylene tanks are different.